The Effectiveness of Phonics Method on Beginning Reading English Ability for Children Aged 4-6 Years - Wulandari, Siska; Prasetyo, Agung; Santoso, Doni Anggoro Ari (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
The aim of this research is to analyze the effectiveness of the phonics method applied for the beginning reading abilities of children aged 4-6 years at the Khalifah Islamic School Kindergarten. This research was carried out through classroom action research, which was carried out on children aged 4-6 years consisting of 2 classes. For each class a sample of 19 students was taken. This research method uses an ex post facto method using a quantitative approach with data analysis techniques using a difference test with ? = 0.05 and dk = n1. With an average final score (X) of 64.39, Median 8.5, Mode 17.5, Variance 92.88, Standard Deviation 9.63, Highest Value 76, and Lowest Value 45, while the result (Y) score final average 11.92, Median 14.7, Mode 15.7, Variance 9.59, Standard Deviation 3.09, Highest value 16, and Lowest value 7. After conducting research and processing the data using the mean difference test The average (t), obtained at 27.47 with the criterion ? = 0.05, obtained at 2.04, thus it can be concluded that tcount > ttable, namely 27.47 > 2.04. This means that the hypothesis used is rejection of Ho, and acceptance of H1. After the author analyzed the data at a significant level of ?=0.05, it can be concluded that there is effectiveness of the phonics method in reading early English for children aged 4-6 years at the Khalifah Islamic School Kebayoran Baru Kindergarten, South Jakarta.